281 EPIDEMIOLOGIC CHARACTERISTICS OF GRAM-POSITIVE AND GRAM-NEGATIVE BLOODSTREAM INFECTIONS IN A TERTIARY NEONATAL INTENSIVE CARE UNIT. Issue 1 (1st January 2007) - Afghani, E.; Afghani, B.; Saisan, R.; Sills, J.
Abstract : Background: Bacteremia remains a major cause of morbidity and mortality in neonatal units. Objective: To analyze the epidemiologic characteristics of bloodstream infections at the University of California, Irvine Neonatal Intensive Care Unit (UCI-NICU) over a 7-year period. Methods: All neonates with positive blood cultures within the first month of life treated at the UCI-NICU between January 1998 and December 2004 were identified and their medical records were reviewed. The risk factors prior to the onset of bacteremia caused by gram-positive and gram-negative organisms were compared. Results: These are summarized in the table . Of 216 episodes of bacteremia, 176 (81%) were caused by gram-positive organisms and 40 (19%) were caused by gram-negative organisms. Conclusions: Gram-positive organisms were the predominant cause of bacteremia in neonates at the UCI-NICU during the first month of life, and risk factors such as intubation, central line placement, surgical procedures, and antibiotic use were more common in patients with gram-positive bacteremia. Because of changing epidemiology of bloodstream infections, continuous surveillance studies to identify risk factors associated with bloodstream infections in neonates will be helpful in developing strategies to prevent and treat such infections.